Implementasi Program Pengembangan Kewirausahaan di Politeknik Negeri Bengkalis - Suharyono Suharyono; Dwi Astuti; Marhadi Sastra; Lidya Wati (Universitas Lancang Kuning, 2022)
The Entrepreneurship Development Program (PPK) is a community service program that aims to create new, independent entrepreneurs. PPK provides opportunities and opportunities for students and alumni of the Bengkalis State Polytechnic to utilize their expertise into business opportunities. The PPK has a positive impact in inspiring people to support the improvement of the campus entrepreneurial ecosystem. Students and alumni with skills that have economic value, are nurtured and prepared to become new entrepreneurs. Through the PPK, new entrepreneurs have been born in the fields of IT, animal husbandry, culinary, animation, creative economy, photogrammetry and geospatial information, MC services, printing, and drone services. The PPK is like a midwife for the birth of new and independent entrepreneurs in Bengkalis Regency.